2023
DOI: 10.2147/jmdh.s410925
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Accreditation Program of the Saudi Central Board for Accreditation of Healthcare Institutions on the Safety Dimension of the Institute of Medicine Quality

Abstract: Background Although hospital accreditation is recognized as a tool for improving healthcare, there are inconsistent results regarding its impact on healthcare quality. In Saudi Arabia, it is mandatory for all Ministry of Health (MOH) hospitals to be accredited by the Central Board for Accreditation of Healthcare Institutions (CBAHI). Purpose This study measured the impact of the CBAHI accreditation program on the Institute of Medicine’s (IOM) safety dimension in Madinah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results of the current study align with those of a prior investigation on the influence of hospital accreditation on patient safety measures in Hail, Saudi Arabia, which discovered that accreditation improved the culture of incident reporting [32]. This result is consistent with a different investigation into Madinah hospitals' understanding of the event reporting system [33]. The CBAHI accreditation program encouraged hospital employees to uphold the safety requirements established by the government, enhancing the quality of treatment and patient safety.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the current study align with those of a prior investigation on the influence of hospital accreditation on patient safety measures in Hail, Saudi Arabia, which discovered that accreditation improved the culture of incident reporting [32]. This result is consistent with a different investigation into Madinah hospitals' understanding of the event reporting system [33]. The CBAHI accreditation program encouraged hospital employees to uphold the safety requirements established by the government, enhancing the quality of treatment and patient safety.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, research studies have shown positive outcomes associated with hospital accreditation in KSA. 14 , 13 For example, a study conducted by Alsaedi et al., in 2019 assessed the impact of accreditation on healthcare quality measures in Saudi Arabian hospitals. The findings revealed that accredited hospitals exhibited improved patient outcomes, including decreased nosocomial infections, and higher rates of the safe use of medications.…”
Section: Current Statusmentioning
confidence: 99%
“…The findings revealed that accredited hospitals exhibited improved patient outcomes, including decreased nosocomial infections, and higher rates of the safe use of medications. 14 …”
Section: Current Statusmentioning
confidence: 99%